2021
DOI: 10.1071/mf20326
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70 (Hsp70) and heat shock transcription factor (Hsf) gene families in

Abstract: Genome-wide characterisation and correlation analysis between gene families and environmental stresses are important for understanding the adaptive evolution of marine animals to various environments. Heat shock protein 70 (Hsp70) and heat shock transcription factor (Hsf) are two important gene families that are associated with abiotic stresses and immune responses. In this study, the evolutionary history and function of Hsp70 and Hsf family genes were investigated in Cynoglossus semilaevis through an exhausti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Heat shock protein 70 (HSP70) gene family members are involved in various housekeeping and stress-related activities in all organisms from bacteria to mammals [ 36 , 37 ]. Due to their important roles, especially in enhancing the response of cells to various stress stimuli, the HSP70 gene family has been extensively studied in a variety of aquaculture species, including invertebrate [ 38 ], bivalve [ 39 ], and multiple teleost species [ 14 , 18 , 19 , 20 , 21 , 23 ]. Nevertheless, a systematic analysis of HSP70 genes in the turbot has been lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat shock protein 70 (HSP70) gene family members are involved in various housekeeping and stress-related activities in all organisms from bacteria to mammals [ 36 , 37 ]. Due to their important roles, especially in enhancing the response of cells to various stress stimuli, the HSP70 gene family has been extensively studied in a variety of aquaculture species, including invertebrate [ 38 ], bivalve [ 39 ], and multiple teleost species [ 14 , 18 , 19 , 20 , 21 , 23 ]. Nevertheless, a systematic analysis of HSP70 genes in the turbot has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a total of 20 HSP70 gene family members have been found in the Boleophthalmus pectinirostris , with most of these genes downregulated after exposure to high concentrations of ammonia [ 20 ]. Furthermore, 14 HSP70 genes have been detected in the Cynoglossus semilaevis through database searches and by manual selection, and expression profiles have demonstrated that most of these gene family members, especially hspa5, showed upregulated expression after exposure to low-salinity stress [ 21 ]. Moreover, a total of 16 HSP70 genes were detected in the genome of the rainbow trout ( Oncorhynchus mykiss ); in addition, an RNA-seq analysis indicated that 4 and 7 HSP70 gene family members showed significantly upregulated expression after heat stress in liver and head kidney tissues, respectively [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in sticklebacks, it has been proposed that some of the marineenvironment-specific advantageous variation can be inherited in clusters as a unit [74]. The differential expression of genes including transcription factors associated with stress response and immune responses has been observed in the tongue sole fish in response to a variation in the salinity content of the water [75]. Both cis-and trans-regulatory variations are suggested to modify the expression patterns of the genes (e.g., GLA and IGFLR1) associated with these processes [70,71,73].…”
Section: Extreme Aquatic Environmentsmentioning
confidence: 99%